Corpo e não-corpo: ressignificando memórias e territórios através da fotoperformance - Erica Si (2020)
Inside the proposal of this dissertation we seek to articulate and bring together, through a transversal analysis in practice, both personal and of some contemporary artists, or in the dialogue between different territories, such as body and non-body, the political, subjectivity, the notions of East and West and in the search for identity as always under construction and transit. Such approaches seek to point to implications and interlocutions between art, philosophy and sociology, to trace an initial panorama for this flow from an autobiographical execution. It also wants to identify and analyze some forms of propagation of such phenomena and developments of contemporary theoretical and artistic concepts, through the analysis of personal artistic presentations together with postures an artistic references such as Ana Mendieta, Chun Hua Catherine Dong, Paulo Nazareth, among others, in which we identified a presence of an artistic body that transits between the categories mentioned above.